Labor Narratives and Identity Construction of Marginalized Women on Social Media Platforms - Wang, Xiaoya (Transactions on Social Science, Education and Humanities Research, 2026)
The nature of digital labor and identity expression of rural women, single mothers, and women with disabilities are influenced by intersecting class and gender constraints on social media platforms. This paper will focus on such marginalized groups and explore the characteristics of their labor stories and the reasoning behind identity formation, and reveal how the platform economy contains structural inequities. This research utilizes in-depth interviews as well as verification of data by using the official reports and 12 field cases. It is found that despite the fact that these women build various identities based on labor narratives, they experience urgent dilemmas such as unclear limits of work, inflexible algorithmic labels, and social shame, which significantly constrain their creative and development space. These narratives have also shifted and moved beyond simple images of survival into conscious expressions of self-worth. In contrast to the support strategies of the mainstream platforms, this paper suggests a holistic strategy of platform power, community-based support, and institutional protections, to provide a practical perspective on enhancing the digital labor opportunities of marginalized women and empowering their identity affirmation.